Managing and Developing Human Resources at the Museum - Vigli, Maria; Panagiotopoulos, Giorgos; Argyropoulou, Maria (Qualitative and Quantitative Methods in Libraries, 2019)
The economic and political "effervescence" at the turn of the 20th century and early 21st century strengthened the strategic management of organizations, focusing on the management and training of human resources, as this sector is linked to their sustainability. Museums and, in general, cultural operators, whether state-owned or private, in their efforts to create an upgraded "micro-environment" that will consistently diffuse knowledge and wisely highlight entertainment within an anthropocentric mentality, adapt to the new reality, by applying effusive practices from other scientific areas. The Museum, as a social space where conceptual misrepresentations, cognitive models and cultures interact, reflects the need for a change in its organizational structure, while at the same time making imperative an effective human resource management which should be reflected in the museum's external functions, from exhibition design to communication practices. Museum experience outlines these processes, making the visitor a recipient and a companion of a reality that is served by an upgraded management model. Our proposal examines whether the Modern Greek museum expresses this logic in a meaningful way, offering a holistic museum experience based on qualitative upgrading through the effective management and education of its human resources.